Comparison of complications associated with the use of three different uterine manipulators (Clermont-Ferrand, VCare, and RUMI II) in total laparoscopic hysterectomy - Aslan, Melike; Yavuzkır, Şeyda (My University, 2021)
Introduction: In total laparoscopic hysterectomy (TLH), uterine manipulators (UM) are utilized to facilitate dissection by moving the uterus. However, some complications may occur during the utilization of a manipulator. The aim of this study is to compare the complications that occur during the utilization of three different manipulators. Materials and Methods: In this retrospectively designed study, 103 patients who underwent TLH due to benign indications were included in the study. All patients were operated by the same two surgeons using the same technique. The patients were divided into three groups according to the manipulators utilized. Group 1 (G1) included patients operated with Clermont-Ferrand UM, Group 2 (G2) included patients operated with RUMI II, and Group 3 (G3) included patients operated with VCare. UM-related complications, duration of operation, estimated amount of bleeding, duration of hospital stay, uterine weight, uterine length, number of myomas, and diameter of the largest myoma were recorded. Results: Uterine weight and mean blood loss were higher in G1 than in G3. There was no significant difference between the groups in terms of uterine perforation. Penetration of the manipulator into the mesorectum occurred in one patient in G1 with Douglas perforation. There were two cervical cup melts in G2 and 1 in G3. Cuff dehiscence occurred in one patient each in G2 and G3. Conclusion: Manipulation of the UM, which is an indispensable instrument of the TLH procedure today, by people with skill and experience and the surgeon’s knowledge on the features and limits of the manipulator used will reduce the risk of UM-related complications.
Keywords: Kadın Hastalıkları ve Doğum; Cerrahi